(untitled) (Inflexion Point Magazine, 2026)
Universities or higher education institutions with large campuses often face difficulties for their academic community to locate and recognize places of interest within their facilities. To facilitate this orientation, maps supported by 3D geographic information systems on the Web (WebGIS 3D) offer an immersive and realistic experience. Although there are previous initiatives that use virtual tours with images and videos or web applications with 3D modeling, few developments have integrated georeferenced3D environments with technologies such as augmented reality for enhance immersion. An effective technological solution is to implement WebGIS 3D systems that allow interactive navigation building searches, and guided routes, facilitating immersion in the real physical environment. This study adopts a mixed methodology. On one hand, a project-based technological development approach was employed to design of a Geographic Information System (GIS) on the Web that provides geodata and 3D models of university campus buildings, georeferenced on 2D satellite. The project integrates technologies such as SketchUp®, ArGIS Pro® and Cesium JS© to facilitate the interactive map use, enhancing user accessibility and experiencewhen moving and familiarizing themselves with the physical space of the university campus. On the other hand, a quantitative strategy was incorporated through a user survey aimed at evaluating the platform’s functionality, usability, and user satisfaction.